Methods of Preparation and Characterization of Cyclodextrin Encapsulated Inclusion Complex : Review - Nitin M. Ghatbandhe; Dr. Priya A. Sangole; Nitesh D. Punyaprediwar; Dr. Rakhi shambharkar; Dr. Ashish K. Kavale; Dr. Ganesh D. Satpute (International Journal of Scientific Research in Science and Technology, 2024)
Inclusion Complex is supramolecular system which is formed by inclusion of the guest molecules into the cavity of host molecule and these molecules are held by intermolecular forces but not by covalent bond. The special characteristic of Cyclodextrins is the ability to form an inclusion complex with viable compounds. This article focuses on the various preparation methods for inclusion complexes, their formation constant, experimental and spectral approaches to demonstrate host-guest interaction. Phase solubility diagram indicated that the solubility of guest molecule increases linearly with CD concentration in AL-type and a stoichiometry of 1:1. The inclusion complex formed by various techniques was characterized by various spectroscopic methods. The study offers a variety of studies that demonstrate how cyclodextrins can be used to enhance the solubility, stability, and effectiveness of synthetic pharmaceuticals as well as their physical, chemical, and biological properties.
Keywords: Cyclodextrin; β-Cyclodextrin; Inclusion Complexes; Solubility; Characterization